Byproduct-based concentrates in Swedish dairy cow diets – evaluation of environmental impact and feed costs. (2nd October 2021) - Lindberg, M.; Henriksson, M.; Bååth Jacobsson, S.; Berglund Lundberg, M.
ABSTRACT: This study compared use of byproduct-based concentrates and a control feed based on cereal grains and soybean meal in dairy cow diets and evaluated effects on the environment and feed costs. To achieve a nutrient-dense feed ration to dairy cows byproducts are commonly combined with cereal grains and protein-rich feeds such as soybean meal. The present analysis was based on experimental data for high-yielding dairy cows showing that feeding concentrate based on byproducts gives similar milk yield as feeding concentrate based on cereal grains and soybean meal. Evaluation of the different concentrates using life cycle assessment showed that using byproducts required less cropland (−35%), reduced carbon footprint (−20%) and lowered eutrophication potential (−20%) compared with the control. Energy use was higher (+30%), due to the need for drying wet byproducts. Feed costs per kg energy-corrected milk did not differ between the feeds, which is beneficial from a sustainability perspective.